PENGARUH MINUMAN ISOTONIK TERHADAP DAYA TAHAN AEROBIK - rika sepriani; Sepriadi Sepriadi (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
The purpose of this research is to prove the benefits of isotonic drinks promised by the manufacturers. This is a quasi-experimental research design involving 20 non-athlete male students. The data were analyzed using t-test.From the data analysis, it was found that there was a significant difference between aerobic endurance before and after drinking isotonic drinks, tobserve (5.398604) > ttable (1.729) at level significant α = 0.05. Based on the result of the research, it can be concluded that isotonic drinks has a significant effect towards students’ aerobic endurance.